Carbohydrate based total synthesis of xestodecalactone B and C: revision of the absolute configuration - Pal, Rita; Rahaman, Hasibur; Gurjar, Mukund K. (Current Organic Chemistry, 2012)
A convergent chiral pool approach for the total synthesis of xestodecalactones B and C was demonstrated in which intramolecular acylation reaction constituted the key step. Synthetic and spectroscopic studies reported herein, suggested that the previously assigned structures of xestodecalactone B and C be interchanged.
Keywords: Chiral pool; Hydroboration; Intramolecular acylation; Pinnick oxidation; Revision of absolute configuration; Xestodecalactone B and C

Hypersilyl substituent in heavier low-valent group 14 chemistry - Gour, Kritika; Bisai, Milan Kumar; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2022)
The isolation of unusual compounds with low-valent main-group elements would not have been possible without the development of a series of sterically demanding ligands with bulky substituents. While early literature recognizes the advent of the sterically demanding tris(trimethylsilyl)silyl (SiMe3)(3)Si- group, also known as hypersilyl group, to stabilize species with new coordination modes for the main group elements, it has largely been more recent studies that have utilized this group for isolating stable compounds with low-valent main-group elements. Such compounds are not only interesting from the structure-bonding point of view but showcase potential for small molecule activation under ambient conditions. This review will cover the recent developments in stabilizing unusual compounds with group 14 elements using the exceptionally strong sigma-donor properties and pronounced steric effects of the hypersilyl moiety, emphasizing their synthesis, structure, and reactivity.
Keywords: Germylenes; Hydroboration; Hypersilyl; silylenes; Stannylenes

Ligand-free MnBr2-catalyzed chemo- and stereoselective hydroboration of terminal alkynes - Pawar, Rameshwar B.; Karmur, Mital H.; Punji, Benudhar (Chemistry-an asian jounrnal, 2024)
Developing simple and benign protocols for synthesizing alkenylboronates is crucial as they are synthetically valuable compounds in various organic transformations. In this work, we report a straightforward ligand-free protocol for synthesizing alkenylboronates via atom-economical hydroboration of alkynes with HBpin catalyzed by a manganese salt. The reaction shows a high level of chemo and regioselectivity for the terminal alkynes and exclusively produces E-selective alkenylboronates. The hydroboration scope is vast, with the resilience of a range of synthetically beneficial functionalities, such as halides, ether, alkenyl, silyl and thiophenyl groups. This reaction proceeds through the involvement of a metal-hydride intermediate. The developed alkenylboronate can be smoothly converted to useful C-C, C-N and C-I bond-forming reactions.
Keywords: alkenylboronates; alkyne; Hydroboration; manganese; stereoselectivity

Ce[N(SiMe3)2]3(THF)3-catal yzed hydroboration of CO2, esters and epoxides with pinacolborane: selective synthesis of methanol in multigram scale - Hossain, Md Jabed; Shah, Brij Kumar; Dash, Soumya Ranjan; Vanka, Kumar; Khan, Shabana (Chemistry-A European Journal, 2025)
In this work, we have reduced CO2 with HBpin to afford borylated methanol product selectively in similar to 99 % yield using Ce[N(SiMe3)(2)](3)(THF)(3) as a catalyst. This led to multigram scale isolation of methanol obtained from CO2 reduction via the hydrolysis of borylated methanol, this establishes the potential of Ce[N(SiMe3)(2)](3)(THF)(3) as an efficient homogeneous catalyst for the bulk scale methanol synthesis. A practical application of this catalytic system was also shown by reducing CO2-containing motorbike exhaust efficiently and selectively. Further, C-O bond activation of esters and epoxides using HBpin and 1-2 mol % of Ce[N(SiMe3)(2)](3)(THF)(3) at 60 degrees C afforded the borylated alcohols in good to excellent yields, which can easily be hydrolysed to the eco-friendly corresponding alcohol. The stoichiometric experiments were performed to prove the formation of in-situ generated cerium hydride [Ce]-H as an active catalyst.
Keywords: Cerium; CO2 reduction; Epoxide; Ester; Hydroboration; Lanthanides